“Left atrial myxoma - A tumor in transit” - U S Dinesh Kumar; Murugesh Wali; Shyam Prasad Shetty; K R Sujay (Annals of Cardiac Anaesthesia, 2019)
Cardiac myxoma is the most common type of primary cardiac neoplasm. Over 70% of all cardiac myxomas originate from the left atrium (LA) and 18% from the right atrium (RA). Most myxomas present with constitutional, embolic, and obstructive manifestations. We are presenting a case where a part of myxoma got embolized intra-operatively. Using trans-oesophageal echocardiography, we were able to diagnose and image the transit of the tumor from the left ventricle to the left atrium. We removed the embolized tumor from the left atrium and prevented a dreaded complication like stroke, mesenteric ischemia, renal infarct or limb ischemia, which would have resulted in increased morbidity or mortality of the patient.